1999
DOI: 10.1590/s1516-14391999000400002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the low corrosion resistant phase formed during the sigma phase precipitation in duplex stainless steels

Abstract: The duplex stainless steels, having a volumetric fraction of 50% ferrite and 50% austenite, conciliate high corrosion resistance with good mechanical properties. But, in many circumstances different phase transformations may occur, such as that responsible for sigma phase precipitation, which make the steel susceptible to localized corrosion. During the sigma phase precipitation a new austenitic phase is formed with a very low corrosion resistance. In the present research the composition of this new austenitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 15 publications
3
42
0
2
Order By: Relevance
“…These fine, dispersed carbides contribute to the creep strength of the alloy. The most susceptible site for the formation of sigma phase is the grain boundaries for its high-energy [42]. In other words, the smaller the size of the area the greater tendency of the formation.…”
Section: Discussionmentioning
confidence: 99%
“…These fine, dispersed carbides contribute to the creep strength of the alloy. The most susceptible site for the formation of sigma phase is the grain boundaries for its high-energy [42]. In other words, the smaller the size of the area the greater tendency of the formation.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was adopted in this work. Several works about this subject are found in literature [1][2][3][4][5][6][7][8][9][10] . These works based on sigma phase kinetics generally considered a theory by Johnson and Mehl 11 , Avrami [12][13][14] and Kolmogorov 15 , the JMAK theory or JMAK modified which may be written as:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this work it will be studied the formation of sigma phase in SDSS in isothermal aging at 700ºC, 750ºC and 800ºC. Several authors 2,6,8,22 found around of 850ºC as the temperature of maximum sigma phase kinetics. We selected temperatures below of 850ºC.…”
Section: Introductionmentioning
confidence: 99%
“…After that (Figures 2h to 2l), the amount of ferrite decreases and the colour of most of the sample becomes bright blue. This decrease in ferrite oxides can be related with the drop in the ferrite phase as a consequence of the formation of new intemetallic phases [17][18][19].…”
Section: In-situ Heat Treatmentsmentioning
confidence: 99%